PREVALENCE AND PREVENTION OF IRON DEFICIENCY ANEMIA IN PREGNANCY IN INDONESIA : A COMPREHENSIVE SYSTEMATIC REVIEW - Yulindar, Vivin; Siman, Pratiwi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Pregnancy-related anemia is a global problem that affects both industrialized and developing nations. This disorder is associated with higher rates of morbidity and death, unfavorable birth outcomes, and delayed infant development. It also has major health ramifications.Aims : This systematic review is to review the prevalence of iron deficiency anemia in Indonesia and way to prevent it.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 47 articles, whereas the results of our search on SAGEPUB brought up 545 articles, our search on SCIENCE DIRECT brought up 2238 articles. The results of the search conducted for the last year of 2014 yielded a total 31 articles for PubMed, 132 articles for SAGEPUB and 985 articles for SCIENCE DIRECT. In the end, we compiled a total of 7 papers, 5 of which came from PubMed, 1 of which came from SAGEPUB and 1 of which came from SCIENCE DIRECT. We included seven research that met the criteria.Conclusion: In summary, pregnant women should be counseled to be mindful of their nutritional intake, especially iron and folic acid supplements, and the bride and groom should be counseled on pregnancy preparedness.